Associations between green space and preterm birth: Windows of susceptibility and interaction with air pollution. (September 2020) - Sun, Yi; Sheridan, Paige; Laurent, Olivier; Li, Jia; Sacks, David A.; Fischer, Heidi; Qiu, Yang; Jiang, Yu; Yim, Ilona S.; Jiang, Luo-Hua; Molitor, John; Chen, Jiu-Chiuan; et al.
Highlights: Exposure to residential green space is associated with decreased risk of PTB. Green space has stronger protective associations with PTB in the second trimester. There are positive interactions between green space and air pollution on PTB. Abstract: Background: Recent studies have reported inconsistent associations between maternal residential green space and preterm birth (PTB, born < 37 completed gestational weeks). In addition, windows of susceptibility during pregnancy have not been explored and potential interactions of green space with air pollution exposures during pregnancy are still unclear. Objectives: To evaluate the relationships between green space and PTB, identify windows of susceptibility, and explore potential interactions between green space and air pollution. Methods: Birth certificate records for all births in California (2001–2008) were obtained. The Normalized Difference Vegetation Index (NDVI) was used to characterized green space exposure. Gestational age was treated as a time-to-event outcome; Cox proportional hazard models were applied to estimate the association between green space exposure and PTB, moderately PTB (MPTB, gestational age < 35 weeks), and very PTB (VPTB, gestational age < 30 weeks), after controlling for maternal age, race/ethnicity, education, and median household income. Month-specific green space exposure was used to identify potential windows of susceptibility. Potential interactions between green space and air pollution [fine particulate matter < 2.5 µm (PM2.5 ), nitrogen dioxide (NO2 ), and ozone (O3 )] were examined on both additive and multiplicative scales. Results: In total, 3, 753, 799 eligible births were identified, including 341, 123 (9.09%) PTBs, 124, 631 (3.32%) MPTBs, and 22, 313 (0.59%) VPTBs. A reduced risk of PTB was associated with increases in residential NDVI exposure in 250 m, 500 m, 1000 m, and 2000 m buffers. In the 2000 m buffer, the association was strongest for VPTB [adjusted hazard ratio (HR) per interquartile range increase in NDVI: 0.959, 95% confidence interval (CI): 0.942–0.976)], followed by MPTB (HR = 0.970, 95% CI: 0.962–0.978) and overall PTB (HR = 0.972, 95% CI: 0.966–0.978). For PTB, green space during the 3rd − 5th gestational months had stronger associations than those in the other time periods, especially during the 4th gestational month (NDVI 2000 m : HR = 0.970, 95% CI: 0.965–0.975). We identified consistent positive additive and multiplicative interactions between decreasing green space and higher air pollution. Conclusion: This large study found that maternal exposure to residential green space was associated with decreased risk of PTB, MPTB, and VPTB, especially in the second trimester. There is a synergistic effect between low green space and high air pollution levels on PTB, indicating that increasing exposure to green space may be more beneficial for women with higher air pollution exposures during pregnancy.